Penerapan Model Kooperatif Tipe Teams Games Tournament Untuk Meningkatkan Keterampilan Membaca Pemahaman Pada Siswa Kelas IV Sekolah Dasar - Wulandari, Intan Desi; Supianto, Supianto (Didaktika Dwija Indria, 2026)
This study aims to enhance the reading comprehension skills of 13 fourth-grade students at SDN 1 Triwarno by implementing the cooperative learning model. Teams Games Tournament (TGT). The students' low reading skills were initially attributed to monotonous conventional teaching methods, which made it difficult for them to concentrate and led to boredom, particularly with long narrative texts. This classroom action research used observation, interviews, documentation, and tests for data collection. The pre-action results showed an average score of 54, with only 23% classical completeness. After the TGT implementation, the average score increased to 69 in the first cycle and 83 in the second cycle. The classical completeness also improved significantly, from 69% in the first cycle to 100% in the second cycle. This increase proves that the TGT model is effective in improving students' reading comprehension outcomes and skills, as well as creating a collaborative and engaging learning environment.